Pengaruh Penerapan Green Accounting dan Ukuran Perusahaan terhadap Kinerja Keuangan (Studi pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode Tahun 2021-2024) - Maryani, Maryani; Hardi, Eja Armaz (ARZUSIN, 2026)
Although studies on green accounting and firm size have been widely conducted, research that specifically examines the influence of both on the financial performance of companies listed on the Jakarta Islamic Index in the most recent period still needs to be expanded. This study aims to analyze the influence of green accounting implementation and firm size on the financial performance of companies listed on the Jakarta Islamic Index for the 2021–2024 period. This study used a quantitative approach with a causal design based on panel data. The sample consisted of 17 companies selected through purposive sampling, resulting in 68 observational data. Data were collected through documentation of companies’ annual reports and financial statements and were then analyzed using panel data regression with the assistance of EViews 13. The green accounting variable was measured using a dummy variable, firm size was measured using the natural logarithm of total assets, while financial performance was measured using Return on Assets (ROA). The results showed that green accounting had no significant effect on financial performance. Firm size also had no significant effect on financial performance. Simultaneously, green accounting and firm size had no significant effect on financial performance. These findings indicate that environmental accounting disclosure and the magnitude of company assets are not yet sufficiently strong in explaining changes in the financial performance of companies listed on the Jakarta Islamic Index. The conclusion of this study confirms that corporate financial performance is not always determined by green accounting implementation and asset scale, thereby providing empirical contributions to the development of studies on environmental accounting and corporate finance based on Islamic indices.